THE EFFECTIVENESS OF ELECTRONIC EVIDENCE IN PROVING THE 2024 GENERAL ELECTION RESULTS - Solkhah Mufrikhah; Deni Gunawan; Muhamad Risal Tawil; Muhammad Taufik Rusydi; Aleksander Sakalessy (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This research is a qualitative research with a descriptive approach. The data used in this article are secondary data that researchers obtain from Scientific Journals, Books, Theses, Dissertations, Theses, News, and other things that are commonly used in every research. The data is collected, then selected and concluded using the SWOT analysistechniquecollection, data selection, data reduction and drawing conclusions. The result in this article show the presence of electronic evidence can indeed make it easier to prove Fraud in the General Election effectively both in the Constitutional Court which adjudicates the dispute over the results of the Presidential and Vice Presidential Elections briefly, namely 14 days, reporting to BAWASLU, and others who have a very short time. Electronic evidence in accordance with its strength as the researcher explained above, is easy to access, easy to obtain, easy to back up, and so on. Moreover, this effectiveness can be further increased supported by the General Election system which is slowly adopting a digital ELECTION system.